Ibnu Battuta, Moroccan Explorer and Contributor to Geography in Indonesia - Rudy Prasetyo; Muhammad Rico; Muhammad Riduan (Demagogi: Journal of Social Sciences, Economics and Education, 2024)
Ibn Battuta was a famous Muslim traveler and jurist in the 14th century because he was known as the greatest adventurer of pre-modern times. The story of his fantastic journey made the Western world respect him as the "Marco Polo of the Muslim World". Ibn Battuta was also a famous Arab poet of his time with his adventures to various corners of the world. The method used in this research is literature study, namely by adjusting research variables to research that is relevant to this study. The results of the research show that the traces of his travel steps have become proof of his reliability as a traveler. One of his works which contains the story of his journey is written in his work entitled Tuḥfatun iNuẓẓār ifī iGharāʾibil iAmṣār iwa iAjāʾibil Asfār which was compiled by Ibnu Juzay, but is often simply called Ar-Rihlah Ibnu Battuta. In his work, Ibnu Battuta wrote down various things he encountered in every city or region he visited, so that he could observe and understand every socio-cultural condition of the local people themselves. With the many places he has visited, it is no longer surprising that he has made a major contribution to various sciences, especially geography, because it was the journey he undertook that ultimately opened up new travel routes and introduced that humans living in this world have a diversity of cultures and social conditions. - particularly in Indonesia, the contribution of this research is to describe Ibn Battuta's journey so that it can become a study and example for all readers in social life.